Pemanfaatan Media Wordwall dalam Meningkatkan Motivasi Belajar Siswa pada Pembelajaran Pendidikan Agama Islam - Riskiyah, Zakiatur; Maghfiroh, Muliatul (Kartika: Jurnal Studi Keislaman, 2026)
This study examines the effectiveness of Wordwall as a digital learning medium in increasing student motivation in Islamic Religious Education learning. The research aims to analyze the implementation of Wordwall media and identify its impact on students’ learning motivation as well as the challenges encountered during its application. This study employed a qualitative approach with a descriptive design. Data were collected through observations, interviews, and documentation involving the principal, Islamic Religious Education teachers, and tenth-grade students of the Industrial Chemical Engineering program at SMK Negeri 1 Tlanakan. Data analysis was conducted using data reduction, data display, and conclusion drawing techniques. The findings reveal that the use of Wordwall significantly enhances students’ learning motivation, as reflected in increased classroom participation, learning enthusiasm, student engagement, and positive learning attitudes. The interactive features of Wordwall contribute to a more dynamic, enjoyable, and student-centered learning environment. However, several challenges were identified, including limited access to digital devices and unstable internet connectivity. These results indicate that Wordwall has strong potential as an effective instructional medium, provided that adequate technological infrastructure and teacher digital competence are continuously strengthened.